Underuse of social-ecological systems: A research agenda for addressing challenges to biocultural diversity. (March 2018) - Mauerhofer, V.; Ichinose, T.; Blackwell, B.D.; Willig, M.R.; Flint, C.G.; Krause, M.S.; Penker, ​M.
Highlights: Underuse as biocultural diversity challenge for social-ecological systems circumscribed. Framework of causes, consequences & strategies concerning underuse conceptualized. Structured cross-continental review on underuse based on this framework provided. Pervasive gap in transcontinental comparative research for underuse identified. Global research agenda on identified gap developed & potential outcomes outlined. Abstract: Conservation is often operationalized as a minimization of human intervention in nature. However, many social-ecological systems depend on human interventions to maintain characteristics of biological diversity. Therefore, reduced use or full abandonment of such systems can diminish rather than enhance biological diversity and its related cultural diversity (biocultural diversity). We link the definition of "underuse" with the extinction rate used in the planetary boundaries framework to support a more objective use of the term. We execute a structured cross-continental review of underuse in social-ecological systems of regions that contain more affluent countries to frame a global research agenda on underuse. Our working approach delineates causes, consequences, and strategies concerning underuse. Based on this comparative review, we identify causes of underuse that are similar in different continents, including globalization, and demographic or structural change in Europe, Japan and Oceania. Conservation paradigms emphasizing wilderness ideals in policies are characteristic of underuse in North America, whereas post-socialist transformation processes characterize underuse in Eastern Europe. Land abandonment and de-intensification of use are a common result, particularly in marginal and protected areas. Consequences of the loss of biocultural diversity include the loss of ecosystem services, traditional knowledge, or landscape amenities. We identified a pervasive gap in transcontinental comparative research that stymies the development of effective strategies to reduce underuse of biological diversity and thereby maintain related cultural diversity. We advocate for a global research agenda on governance approaches that address the challenges of underuse. Within this agenda, we emphasize the need for an international cross-case synthesis and a trans-continental mapping of state and civil society-based interventions and co-management approaches to re-establish humans as parts of ecological systems. Such comparative work on best practice cases in a real-world context should enhance adaptive management of biocultural diversity and prevent extinction caused by underuse. Thus, this innovative connection between underuse and the planetary boundary extinction rate, along with our new global research agenda on underuse, should initiate much needed support for policy makers and natural resource managers who must decide on appropriate types and levels of human intervention to implement, both inside and outside of protected areas.